Soglie di eccedenza Forme di resistenza estetica nell’era algoritmica (Itinera, 2025)
This paper investigates the aesthetic role of algorithmic hallucinations, situating Heidegger’s question of technology at the core of its analysis. Algorithmic hallucinations are approached not as accidental malfunctions, but as instances of computational poiēsis, in which algorithmic systems disclose phenomena that exceed the bounds of predictive models. They constitute moments of excess within the calculable, revealing the unforeseen and the incalculable as intrinsic dimensions of technical processes. Margaret Boden’s framework of transformative creativity situates these phenomena as generative acts capable of producing configurations of meaning that transcend the limitations of their inputs, highlighting the aesthetic resistance inherent in algorithmic systems. Concurrently, Jacques Rancière’s notion of the partage du sensible illuminates the political dimension of such events, demonstrating how hallucinations destabilize established regimes of visibility and recognition. Integrating these perspectives, the study underscores the dual significance of unpredictability in algorithmic systems: as an aesthetic edge, it discloses the system’s capacity for excess, invention, and perceptual surprise; as a political edge, it exposes the fragility of imposed structures of perception. The paper concludes by examining contemporary artistic practices that critically engage algorithmic systems, showing how they translate the unforeseen and the incalculable into forms of aesthetic resistance and perceptual innovation.